Tolerogenic dendritic cells and regulatory T cells: A two-way relationship - Mahnke, Karsten; Johnson, Theron S.; Ring, Sabine; Enk, Alexander H. (Journal of dermatological science, 2007)
At first glance, dendritic cells (DCs) and regulatory T cells (Tregs) do not have much in common. DCs are characterized by their unsurpassed T cell stimulatory capacity, whereas Tregs are marked by the ability to suppress proliferation of effector T cells. However, only mature/activated DCs stimulate T cell proliferation, whereas immature DCs induce Tregs. This provides a means by which peripheral tolerance is maintained: in the absence of inflammation and disease, DCs encounter apoptotic cells and “self” detritus in peripheral tissues. Thus, DCs constantly sample the peripheral environment and, accordingly, the presentation of “self” by these steady state DCs results in induction of suppressive Tregs. Vice versa, Tregs are able to affect DC development, preventing maturation and inducing IL-10, as well as immunosuppressive molecules of the B7-H family, in DCs. Therefore, these novel findings establish a mutual interaction between DCs and Tregs for the upkeep of immunosuppression: immature DCs induce Tregs and inversely Tregs prepare DCs to become immunosuppressive, thereby extending the immunosuppressive function of Tregs. The possible means of cellular interactions as well as the consequences for tolerance and immunity are discussed in this review.